Morphological and molecular analysis of Willowsia nigromaculata (Collembola, Entomobryidae, Entomobryinae) reveals a new cryptic species from the United States - Cipola, Nikolas G.; Katz, Aron D. (European Journal of Taxonomy, 2021)
Commonly reported as a household pest throughout the northern hemisphere, Willowsia nigromaculata (Lubbock) is among the most abundant and widely distributed springtails. However, taxonomic uncertainty due to incomplete morphological descriptions based on specimens from different continents may lead to incorrect identifications and/or prevent the recognition of distinct lineages within this morphospecies. Here, we perform the first comprehensive morphological and genetic comparison between W. nigromaculata specimens collected from North America and Europe. Morphological and genetic evidence reveals that populations in the United States and France represent two distinct nigromaculata-like species, but a phylogenetic analysis indicates both species may also be present in Canada. Based on these results, we redescribe W. nigromaculata from France, provide a description for Willowsia neonigromaculata sp. nov. from the United States, and propose new diagnostic characters for their separation, including the number of inner appendages on the maxillary sublobal plate. We also highlight the need for morphological and molecular investigations of additional populations to better understand the diversity and distribution of W. nigromaculata and related species.